Acyl-CoA Synthetase 5 Promotes the Growth and Invasion of Colorectal Cancer Cells. (20th July 2017) - Ding, Shihua; Tang, Shaohui; Wang, Min; Wu, Donghai; Guo, Haijian
Abstract : Background and Aims . Acyl-CoA synthetase 5 (ACS5) has been reported to be associated with the development of various cancers, but the role of it in colorectal cancer (CRC) is not well understood. The present study aimed to explore the potential role of ACS5 in the development and progression of CRC. Methods . ACS5 expression in CRC tissues and CRC cell lines was examined, and its clinical significance was analyzed. The role of ACS5 in cell proliferation, apoptosis, and invasion was examined in vitro. Results . We found that ACS5 expression was upregulated in CRC cells and CRC tissues and that high ACS5 expression was more frequent in CRC patients with excess muscular layer and with poor tumor differentiation. Furthermore, knockdown of ACS5 in HT29 and SW480 cells significantly dampened cell proliferation, induced cell apoptosis, and reduced cell migration and invasion. In contrast, the ectopic overexpression of ACS5 in LOVO and SW620 cells remarkably promoted cell proliferation, inhibited cell apoptosis, and enhanced cell migration and invasion. Enhanced cell growth and invasion ability mediated by the gain of ACS5 expression were associated with downregulation of caspase-3 and E-cadherin and upregulation of survivin and CD44. Conclusions. Our data demonstrate that ACS5 can promote the growth and invasion of CRC cells and provide a potential target for CRC gene therapy.